Ginkgolide B ameliorates oxidized low‐density lipoprotein‐induced endothelial dysfunction via modulating Lectin‐like ox‐LDL‐receptor‐1 and NADPH oxidase 4 expression and inflammatory cascades. (22nd August 2018) - Feng, Zhanbin; Yang, Xiaofei; Zhang, Long; Ansari, Irfan A.; Khan, M. Salman; Han, Shuyi; Feng, Yaoyu
Abstract : The current study was undertaken to delineate the protective effect of Ginkgolide B, a phyto‐constituent from Ginkgo biloba, on oxidized (ox)‐LDL‐induced endothelial dysfunction via targeting Lectin‐like ox‐LDL‐receptor‐1 (LOX‐1), NADPH oxidase 4 (NOX‐4), and other inflammatory proteins. Our results have shown that Ginkgolide B downregulated the expression of LOX‐1 in ox‐LDL‐treated human umbilical vein endothelial cells (HUVECs) and RAW246.7 murine macrophages which ultimately resulted in decreased cholesterol deposits in HUVECs and RAW264.7. Moreover, Ginkgolide B suppressed the enhanced NOX4 expression, which was associated with attenuation of ROS generation in ox‐LDL‐stimulated HUVECs and RAW264.7 cells. Ginkgolide B also ameliorated the endothelial dysfunction by inhibiting the augmented expression of monocyte chemotactic protein‐1 (MCP‐1), intercellular adhesion molecule‐1 (ICAM‐1), and vascular cell adhesion molecule‐1 (VCAM‐1) in ox‐LDL‐activated HUVECs. Furthermore, the enhanced expression of many inflammatory cytokines in ox‐LDL‐induced RAW264.7 macrophages, both at transcription and protein level, was significantly down‐regulated after Ginkgolide B treatment. Ginkgolide B also illustrated atheroprotective property via suppressing the augmented expression of matrix metalloproteinase‐1 and cyclooxygenase‐2 in ox‐LDL‐stimulated RAW264.7 macrophages. In summary, our study has established that Ginkgolide B ameliorates endothelial dysfunction via targeting LOX‐1, NOX‐4, MCP‐1, ICAM‐1, and VCAM‐1 along with the markers associated with inflammatory cascades and thus could be promoted as a valuable therapeutic agent in prevention and management of atherosclerosis.